Pre-connected sets in Bitopological Spaces - Erees, Alaa (University of Thi-Qar Journal of Science, 2008)
n this paper,we give and study a generalization for the concept "pre-connected set" in bitopological spaces , through as well as wegive several various results related to this generalization .